2007
DOI: 10.1681/asn.2005090966
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance–Associated Protein 4 Is Involved in the Urinary Excretion of Hydrochlorothiazide and Furosemide

Abstract: The role of ATP-binding cassette transporters in the urinary excretion of diuretics was investigated. Significant ATPdependent uptake of hydrochlorothiazide (HCT) and furosemide was observed in membrane vesicles that expressed multidrug resistance-associated protein 4 (MRP4) and breast cancer resistance protein (BCRP). Unlike taurocholate uptake, S-methylglutathione had no effect on the ATP-dependent uptake of both compounds by MRP4. The functional importance of MRP4 and BCRP in the urinary excretion of HCT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 31 publications
3
80
0
Order By: Relevance
“…32 Decreased Met levels with altered DNA methylation may contribute to kidney injury because stimulation of HGF signaling reduces interstitial fibrotic changes in the diabetic kidney. 20 Persistent changes in mRNA levels with altered DNA methylation of Abcc4, which is involved in the urinary excretion of drugs such as furosemide and thiazides, 33 and of Slco1a1, another transporter, potentially induce alterations in drug pharmacokinetics and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…32 Decreased Met levels with altered DNA methylation may contribute to kidney injury because stimulation of HGF signaling reduces interstitial fibrotic changes in the diabetic kidney. 20 Persistent changes in mRNA levels with altered DNA methylation of Abcc4, which is involved in the urinary excretion of drugs such as furosemide and thiazides, 33 and of Slco1a1, another transporter, potentially induce alterations in drug pharmacokinetics and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus Oat1 Ϫ/Ϫ and Oat3 Ϫ/Ϫ mice present a very similar rightward shift in the dose-natriuresis curves for both bendroflumethiazide and furosemide (11). Previous studies showed that mice lacking the multidrug resistance-associated protein 4 (MRP4), which localizes to the apical membrane of the proximal tubule, have a reduced renal clearance of furosemide and hydrochlorothiazide, but other transporters maintain a significant efflux into the proximal tubule lumen in these mice without fully compensating for the absence of MRP4 (14). Our studies indicate that both OAT1 and OAT3 contribute to basolateral uptake, and thus renal secretion, of furosemide and thiazide diuretics in vivo and that lack of either one is not fully compensated by the other.…”
Section: Impaired Natriuretic Response To Bendroflumethiazide In Oat1mentioning
confidence: 98%
“…Because thiazide diuretics act in the tubular lumen, their action requires successful delivery to the DCT. This is mediated by active secretion of thiazide diuretics in the proximal tubule through organic anion transporter and multidrug resistance-associated protein 4 [39,114]. This explains why a reduction in glomerular filtration rate results in reduced efficacy of thiazide diuretics.…”
Section: Drugs Inhibiting Nccmentioning
confidence: 99%